2012
DOI: 10.1159/000337262
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction after Pulmonary Resection for Lung Cancer: A Multicenter Comparative Analysis

Abstract: Background: Patient satisfaction reflects the perception of the customer about the level of quality of care received during the episode of hospitalization. Objective: To compare the levels of satisfaction of patients submitted to lung resection in two different thoracic surgical units. Methods: Prospective analysis of 280 consecutive patients submitted to pulmonary resection for neoplastic disease in two centers (center A: 139 patients; center B: 141 patients; 2009–2010). Patients’ satisfaction was assessed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…Confounding factors may be present among our patientd including personality types and educational level. Distressed personality types report lower satisfaction and that they have been given less information and those with higher educational levels report lower satisfaction [ 18 , 19 ]. Intrapersonal comparison should reduce the impact of these in comparing responses across time; in addition the fact that free text responses and binary regression analysis identified similar topics of importance supports the findings being real and not due to a statistical phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Confounding factors may be present among our patientd including personality types and educational level. Distressed personality types report lower satisfaction and that they have been given less information and those with higher educational levels report lower satisfaction [ 18 , 19 ]. Intrapersonal comparison should reduce the impact of these in comparing responses across time; in addition the fact that free text responses and binary regression analysis identified similar topics of importance supports the findings being real and not due to a statistical phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Patient satisfaction with hospital care reflects the perception of the patient of the quality of care they receive during their hospitalisation (Kullberg et al, 2015;Wentlandt et al, 2016). Most research on patient satisfaction with end-of-life care in the hospital has been conducted in specific settings, such as a palliative care unit or an oncology department (Arora et al, 2010;Bredart et al, 2009;Buzgova, Hajnova, Sikorova, & Jarosova, 2014;Dy et al, 2008;Nguyen et al, 2014;Seccareccia et al, 2015;Wentlandt et al, 2016) or in patients with a specific type of cancer, such as gynaecologic cancer or lung cancer (Plotti et al, 2015;Pompili et al, 2013;Skret-Magierlo, Ras, Barnas, & Skret, 2016). Little is known about satisfaction with inhospital care of patients with advanced cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Among the three attributes examined in our study, thoroughness reflects patients' perception of technical quality, while listening and explanation reflect the quality of interpersonal communication. Few studies have evaluated the impact of perceived technical quality on satisfaction [16,22,23], and none used nationally representative data. A study using data collected in Indianapolis in the late 1990s concluded that physician ability to provide explanations to patients and the length of time spent with the doctor exerted a stronger influence on satisfaction than did thoroughness of care [6].…”
Section: Resultsmentioning
confidence: 99%
“…Very few studies have extended PCC evaluations to the technical quality of care (such as thoroughness), which may capture aspects of services received more objectively than quality of communication [6]. The literature consistently distinguishes the interpersonal aspects of quality from the technical aspects, suggesting they are best considered as distinct service components [16][17][18]. As a consequence, their effect on patients' perceptions of quality and satisfaction may differ.…”
Section: Introductionmentioning
confidence: 99%